American lobster (Homarus americanus) hepatopancreas transcriptome reveals the significance of chitin-related genes during impoundment shell disease - Nicolas Argenta; Marianna Rampaul; K. Fraser Clark (FACETS, 2024)
American lobsters (Homarus americanus) stored in open tidal pounds can develop impoundment shell disease (ISD), resulting in decreased marketability of the lobsters on the live market. Little is known about ISD or the immunological responses of lobsters exhibiting this disease. The objective of this project was to identify genes from H. americanus hepatopancreas that are differentially expressed in response to ISD. Lobsters were separated into asymptomatic, moderately symptomatic, and severely symptomatic groups, which represent animals with 0%, 5%–20%, and >20% lesion coverage of the carapace, respectively. RNA-seq analysis found that 134 genes were differentially expressed between groups (false discovery rate (FDR) < 0.05). Most, 80, of these genes were found exclusively in the comparison between moderately symptomatic and asymptomatic groups. All animals clustered in their proposed groups based on the expression of the differently expressed genes (DEGs), and the asymptomatic group clustered as an out-group. The expression of most DEGs was higher in the asymptomatic group than the others, which could be related to a stronger response against the disease or differences in individual resistance against ISD development. Among these genes, we highlight eight chitin-related genes, one α-2-macroglobulin-like gene, one acute phase serum amyloid A gene, one pseudohaemocyanin gene, and one trypsin-1-like gene.